Availability Assessment of Steam and Gas Turbine Units of a Thermal Power Station Using Markovian Approach - Christian Emeka Okafor; Augustine A. Atikpakpa; Ugochukwu Chuka Okonkwo (Archives of Current Research International, 2017)
Aims: The aim of this study is to assess the availability of steam and gas turbine units of a thermal power station using Markovian Approach. Place and Duration of Study: Operational data from 2003 to 2012 were collected from a thermal power station in Nigeria. These raw data represents records of plant generation capabilities as well as other inherent daily conditions that will enhance the success of this study. Methodology: Relevant indices such as Repair Rate (μ), Failure Rate (λ), Mean Time to Repair (MTTR), Mean Time to Failure (MTTF) and Mean Time Between Failures (MTBF) was determined for each of these states. For each state, state probability are also calculated through repair rate and failure rate of the corresponding state. Results: The repair rate for ST01, ST02 and ST06 in terms of assessment in the period studied is high, particularly ST01 and ST06. But for 2008 and 2011, ST02 was completely unavailable. the station availability figures of ST01 for the year 2003 is 0.929 and its failure rate (λ) is 0.0478 in 83.7 hrs; repair rate was 0.64 and failure rate (λmax) for ST06 is 0.1396 in 2007 while the repair rate is 0.7862 in 72.5 hrs. For the year 2007, ST02 (λmin) has failure rate of 0.05308 in 113 hrs while, ST02, GT01, GT02 in ∞hrs is nil (completely unavailable) between year 2008 to 2011; ST06 has failure rate (λ) of 0.1163 in 52 hrs in 2006 while the repair rate was 0.1806. Effects of leakages along the lines is most paramount in the entire unit with ST01and ST06 most affected 762hrs and 2568 respectively. Conclusion: For the thermal power station to be reliable, the failure rate of equipment must be reduced to the barest minimum. Repair rate for assessment must be high to guarantee plant efficiencies.